2019
DOI: 10.1016/j.jgg.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Organelle aging: Lessons from model organisms

Abstract: Most cellular processes descend into failure during aging. While a large collection of longevity pathways has been identified in the past decades, the mechanism for age-related decline of cellular homeostasis and organelle function remains largely unsolved. It is known that many organelles undergo structural and functional changes during normal aging, which significantly contributes to the decline of tissue function at old ages. Since recent studies have revealed an emerging role of organelles as regulatory hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 202 publications
(269 reference statements)
0
9
0
Order By: Relevance
“…In the transient mTor knockdown group, 327 genes were significantly differentially spliced, compared to 17 of continuous mTor knockdown and 4 specific to mTor knockdown in late life. KEGG analysis in the transient mTor knockdown group were enriched for differentially spliced variants associated with endocytosis 39 , the lysosome 40 , Hippo signalling (potentially mediating longevity through autophagy 41 and FOXO 42 ) and mTor signalling itself (Table S7). Thus, potentially the long-lasting mortality benefits from transient mTor reduction are mediated by long-lasting changes in alternative splicing, as predicted from the upregulation of the spliceosome 43 .…”
Section: Resultsmentioning
confidence: 99%
“…In the transient mTor knockdown group, 327 genes were significantly differentially spliced, compared to 17 of continuous mTor knockdown and 4 specific to mTor knockdown in late life. KEGG analysis in the transient mTor knockdown group were enriched for differentially spliced variants associated with endocytosis 39 , the lysosome 40 , Hippo signalling (potentially mediating longevity through autophagy 41 and FOXO 42 ) and mTor signalling itself (Table S7). Thus, potentially the long-lasting mortality benefits from transient mTor reduction are mediated by long-lasting changes in alternative splicing, as predicted from the upregulation of the spliceosome 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Researches demonstrated that during the aging, RC function is compromised which might be due to a high level of accumulated ROS from altered metabolic process and weakened antioxidant defense. However, the induction of mitohormesis to prevent age-related diseases at young age and manipulation of RC activity to prolong lifespan in latelife through pharmaceutics will be a promising avenue to pursue (Bouska et al, 2019).…”
Section: Mitochondrial Rosmentioning
confidence: 99%
“…From their biosynthesis to their trafficking and degradation, proteins are controlled through different mechanisms including molecular chaperone networks and the ubiquitin-proteasome system (UPS) in the ER (3,13,18). The functioning of these mechanisms has been shown to be impaired with age in different organs including skin, liver, heart, brain, spleen, and lung (3,19,20). In the ER, chaperones such as calnexin, calreticulin, and binding immunoglobulin protein (BiP) [also known as glucose-regulated protein-78 (GRP78)] recognize and bind nascent and misfolded proteins to prevent their aggregation (21,22).…”
Section: Er Stress and Relation With Agementioning
confidence: 99%
“…However, over 90% of misfolded and damaged proteins are cleared through the UPS, which is a highly selective process as it degrades exclusively ubiquitinated proteins (13). As the protein quality control network of the cell, the UPS is crucial for the degradation of misfolded or unfolded and damaged proteins (19,29). However, this mechanism becomes impaired with age (13).…”
Section: Er Stress and Relation With Agementioning
confidence: 99%